The Effect of Store Atmosphere and Location on Purchase Decisions in Bengkulu City Mode Shopping - Wiwit Tea Ochty Sri Wulandari; Karona Cahya Susena; Sri Handayani (Journal of Indonesian Management, 2022)
The purpose of this study was to determine the effect of store atmosphere and location on purchasing decisions at the City of Bengkulu City. The sample in this study was 65 female customers at the Fashion Squire in Bengkulu City. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of multiple regression have the equation Y = 7.005 + 0.512 (X1) + 0.295 (X2) + e, because the direction of the regression is positive, it can be interpreted that if the store atmosphere and location increase, purchasing decisions at the Bengkulu City skipper will also increase. Store atmosphere is more influential than location on purchasing decisions because the store atmosphere regression value is 0.512 greater than the location regression value. Store atmosphere has a significant effect on consumer purchasing decisions at the City of Bengkulu City skipper, this is evidenced by the results of the t-test showing the value of tcount is greater than ttable (6.256>1.669) and a significant value of 0.000 <0.05 means H_0 is rejected and H_a is accepted. Location has a significant effect on consumer purchasing decisions at the City of Bengkulu City skipper, this is evidenced by the results of the t-test showing the value of tcount is greater than ttable (4,477>1,669) with a significant value of 0.000 <0.05, meaning H_0 is rejected and H_a is accepted. Store atmosphere (X_1) and Location (X_2) together have a significant effect on consumers' purchasing decisions (Y) at the City of Bengkulu City skipper, this is evidenced by the F test showing the value of Fcount > Ftable (146,677> 3.99) with a value of significant at 0.000.